PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA DINAS LINGKUNGAN HIDUP KABUPATEN MALINAU PROVINSI KALIMANTAN UTARA - Toni Salsius; Ibnu Sabil; Agus Priyanto (Media Bina Ilmiah, 2025)
This research aims to analyze the influence of leadership style, motivation, and work discipline on employee performance at the Environmental Office of Malinau Regency. The phenomenon underlying this study is the suboptimal organizational performance achievement reflected in punctual attendance rates of 72.6%, timely work program completion of 70%, and individual performance target achievement of 61%. The research method employed a quantitative approach using survey techniques with 100 employee respondents. The research instrument consisted of questionnaires that had been tested for validity and reliability. Data analysis utilized multiple linear regression with statistical software assistance. Research findings indicated that all variables met classical assumption tests including normality, multicollinearity, and heteroscedasticity. Hypothesis testing proved that leadership style, motivation, and work discipline significantly influenced employee performance both partially and simultaneously with significance values of 0.000 < 0.05. The formed regression equation was Y = 2.997 + 0.222X₁ + 0.390X₂ + 0.361X₃, where motivation had the greatest influence (β = 0.390), followed by work discipline (β = 0.361), and leadership style (β = 0.222). The coefficient of determination of 71.3% demonstrated that the three independent variables could explain employee performance variation. Research findings confirmed the importance of synergy between effective leadership, high motivation, and consistent discipline in achieving optimal performance. The practical implications of this research emphasize the need to focus on motivation enhancement as the primary priority, followed by strengthening work discipline and developing adaptive leadership styles to optimize employee performance in public administration environments